Uterine natural killer cells in patients with idiopathic recurrent miscarriage - Kuon, Ruben-Jeremias; Strowitzki, Thomas; Toth, Bettina (American journal of reproductive immunology, 2017)
Problem Uterine natural killer (uNK) cells are major players during implantation and early pregnancy. The aim of our study was to analyze uNK cell concentration in the endometrium of idiopathic recurrent miscarriage (iRM) patients and fertile controls. Method of study Out of n=130 couples with ≥3 consecutive, clinical RM screened according to a standardized diagnostic protocol, n=58 patients with iRM were identified. Endometrial biopsies were investigated in patients and n=17 fertile women (controls) via immunohistochemistry. Results Compared to controls, the concentration of uNK cells was significantly higher in iRM patients (257±212 vs. 148±73 uNK cells/mm², P=.04). IRM patients showed a higher prevalence of >300 uNK cells/mm² than controls (34.5% vs. 5.9%, P=.02). In 88% of controls and 62% of iRM patients, uNK cells were detected within the range of 40-300/mm². Conclusion Idiopathic recurrent miscarriage patients showed higher uNK cell levels than controls supporting the possible impact of uNK cells in the pathophysiology of miscarriage. Our cutoff levels might help to select RM patients which may benefit from immunomodulatory treatment.